Comparison of Unlawful Acts in Criminal Law and Civil Law in Indonesia - Verdy Hengky Kalele; Zainal Arifin Hosein (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to analyze the comparison between unlawful acts (PMH) in criminal law and civil law in Indonesia, focusing on the differences in definitions and the elements that constitute unlawful acts in both legal systems, as well as the implications of the application of PMH in each field of law. The research method used is normative juridical, with legislative and conceptual approaches to examine the provisions in the Criminal Code (KUHP) and the Civil Code (KUHPer). This study identifies fundamental differences in objectives, sanctions, and legal subjects involved, as well as their impact on individual and societal interests. The research findings show that although there are similarities in the basic principles regulating PMH, significant differences lie in the nature of the sanctions imposed, where criminal law emphasizes prevention and punishment, while civil law focuses on compensation and recovery of losses. This research provides insights into how these two legal systems complement each other in maintaining justice and order in Indonesia.